Role of Cryoprotectants in Preventing Quality Loss of Goat Oocytes after Warming by Examining Insulin-Like Growth Factor-1 and Bone Morphogenetic Protein-15 Expression - Shabira, Zahra; Widjiati, Widjiati; Rimayanti, Rimayanti; Lestari, Tita Damayanti; Safitri, Erma; Mafruchati, Maslichah; Hendrawan, Viski Fitri (Jurnal Medik Veteriner, 2025)
This research aimed to assess the efficacy of ethylene glycol-sucrose as an alternative cryoprotectant compared to commercial cryoprotectants by focusing on the expression of insulin-like growth factor-1 (IGF-1) and bone morphogenetic protein-15 (BMP-15) in goat oocyte cumulus complexes after warming with identification using the immunocytochemical analysis. Maturated oocytes were divided into 3 groups, i.e., (C) the control group followed by an immunocytochemical examination, and two treatment groups, i.e., (P1) was exposed to a commercial cryoprotectant for 15 minutes, then placed in a hemistraw and dipped in liquid nitrogen, and (P2) was exposed to 30% ethylene glycol and 1 M sucrose for 15 minutes, then placed in a hemistraw and dipped in liquid nitrogen. The results revealed divergent responses in IGF-1 (CG = 9.00 ± 3.00; P1 = 9.50 ± 3.20; P2 = 4.67 ± 0.94) and BMP-15 (CG = 10.50 ± 3.35; P1 = 9.50 ± 2.69; P2 = 5.50 ± 3.64) expression patterns, possibly influenced by the two cryoprotectant abilities and oocytes performing their permeabilities to cryoprotectant solution. We concluded that each cryoprotectant is necessary to mitigate the adverse impact on gene expression in oocytes so that we can use it for reproductive technologies.